Spatialised Social Accounting and its application in the Greater South East of England - Vadim Grinevich; Ying Jin; Vassilis Zachariadis (European Regional Science Association (ERSA), 2010)
The paper presents a new extension to the Social Accounting Matrix (SAM) in the assessment of land use, transport and utility infrastructure development options from the perspective of a UK region. A geographically detailed model is required to analyse spatially heterogeneous impacts of land use, transport and utility infrastructure developments. On the other hand, a robust assessment must be built upon a systematic representation of the links among production, consumption, investment and trade such as in a SAM. A spatialised SAM has thus been developed. The paper discusses the methodological and empirical approach, focusing on model calibration at the Base Year, empirical testing of the projection procedure, and the new insights this model offers into the effects of policy and technology options on the demand for land, travel, water, energy , emissions and waste disposal.
Keywords: 330; Land-use - transport interaction; household location; Input -Output tables; Social accounting; random utility models